The Effect of Locus of Control on the Quality of Education in Lokhsumawe Moderated by Compensation - Ahmad; Syaifuddin; Fajar Rezeki Ananda Lubis (Universitas Muhammadiyah Surabaya, 2025)
The quality of education is very much needed to improve human resources. Therefore, this study will test whether there is an influence of locus of control on the quality of education in Lokhsumawe which is moderated by compensation. This study uses quantitative methods. The results of the study indicate that Locus of Control has an influence on the quality of education in Lokhsumawe. They also show that Locus of Control has an influence on compensation, and compensation has an influence on the quality of education. The research variables also conclude that teacher compensation affects Locus of Control on the quality of education in Lhoksumawe City High Schools.